2022
DOI: 10.1126/sciadv.abj7110
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism confers tolerance to cerebral malaria

Abstract: The modulation of the host’s metabolism to protect tissue from damage induces tolerance to infections increasing survival. Here, we examined the role of the thyroid hormones, key metabolic regulators, in the outcome of malaria. Hypothyroidism confers protection to experimental cerebral malaria by a disease tolerance mechanism. Hypothyroid mice display increased survival after infection with Plasmodium berghei ANKA, diminishing intracranial pressure and brain damage, without altering pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Our interpretation is supported by a recent study 37 on protective effects of hypothyroidism in ECM. In hypothyroid C57BL/6 wt mice, PbA infections did not result in increased intracranial pressure and edema despite inflammation and BBB-breakdown.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our interpretation is supported by a recent study 37 on protective effects of hypothyroidism in ECM. In hypothyroid C57BL/6 wt mice, PbA infections did not result in increased intracranial pressure and edema despite inflammation and BBB-breakdown.…”
Section: Discussionsupporting
confidence: 90%
“…In these mice the flow in the large vessels, as determined with TOF-MRA, was maintained. Although angiographies were not analyzed at the single-vessel level, the flow in the sinuses is clearly visible in these TOF-MRA images 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Malaria is a life-threatening infection caused by the genus Plasmodium . A recent study using a mouse model of cerebral malaria showed that hypothyroidism promotes mouse survival, with protection attenuated by the SIRT1 inhibitor EX-527, whereas in mice with normal thyroid function the SIRT1 activator SRT1720 confers host protection [ 83 ], thus suggesting SIRT1 as a therapeutic target in cerebral malaria.…”
Section: Function Of Sirt1 During Infectionsmentioning
confidence: 99%
“…Thermoregulation is a key feature in the maintenance of homeostasis that allows organ processes to work effectively, and its close connection with thyroid hormones is well-documented 1 , 2 . With an increase in metabolic diseases in recent years, thyroid dysfunctions, especially hypothyroidism, represent the most common endocrine disorders and are a major healthcare issue that affects ~4–10% of the population worldwide 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%